SUCCESSOR SYSTEMS: THE ROLE OF REFLEXIVE ALGORITMS IN ENACTING IDEOLOGICAL CRITIQUE - Geiger, R. Stuart (AoIR Selected Papers of Internet Research, 2014)
This paper extends Harding (1987) and Haraway’s (1988) call for “successor sciences” - - ways of knowing that critically blend objectivity with situatedness – to the study of algorithms (e.g. Gillespie 2014). “Successor systems” critique dominant modes of knowledge production by computationally supporting alternative modes, reflectively deploying algorithmic routines to build “a better account of the world” (Haraway, 579). This paper analyzes three activist projects as successor systems, discussing political and epistemological implications of such tactics.